TRANSFORMING BUSINESS ADMINISTRATION: THE ROLE OF INFORMATION TECHNOLOGY IN MODERN PRACTICES - Jun, Li Wei; Hua, Zhou Ming (Ayden Journal of Management and Social Sciences, 2024)
Drawing upon insights from contemporary literature and empirical studies, this paper elucidates the multifaceted role of information technology in reshaping business administration paradigms. It delves into various facets of IT utilization, ranging from enterprise resource planning systems and customer relationship management platforms to data analytics tools and cloud computing solutions. Furthermore, the paper examines the transformative potential of emerging technologies such as artificial intelligence, blockchain, and the Internet of Things, highlighting their implications for organizational performance and strategic decision-making. Through a comprehensive analysis, this paper offers practical insights for businesses seeking to harness the power of information technology to drive organizational excellence and competitive advantage. It advocates for strategic alignment between IT investments and business objectives, emphasizing the need for proactive adaptation to technological advancements and digital disruptions. By embracing a culture of innovation and digital transformation, enterprises can unlock new opportunities, mitigate operational challenges, and foster sustainable growth in the dynamic business landscape of the 21st centur